1980
DOI: 10.1288/00005537-198011000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical studies of the posterior petrous apex with regard to hearing preservation in acoustic neuroma removal

Abstract: Some surgeons have shown that tumors of the internal auditory canal and cerebellopontine angle may be removed with preservation of hearing through the suboccipital approach. If hearing is to be conserved, the cochlear division of the VIIIth cranial nerve and blood supply of the labyrinth must be preserved. In addition, surgical entry into the labyrinth, upon removal of the posterior wall of the internal auditory canal, must be avoided since it is likely to result in permanent sensorineural hearing loss. Carefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 1 publication
0
31
0
1
Order By: Relevance
“…In a left lateral position, the head fixed in a clamp in each animal a right lateral craniectomy of the posterior fossa was performed. Care was taken not to retract the cerebellum or to open the labyrinth, because both factors might disturb the BAEPs [9,[32][33][34]. The pre-operative BAEPs were used as the standard measurement.…”
Section: Methodsmentioning
confidence: 99%
“…In a left lateral position, the head fixed in a clamp in each animal a right lateral craniectomy of the posterior fossa was performed. Care was taken not to retract the cerebellum or to open the labyrinth, because both factors might disturb the BAEPs [9,[32][33][34]. The pre-operative BAEPs were used as the standard measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Some anatomical and radiological studies suggested the impossibility of exposing the fundus of the IAC without violating the semicircular canals, the vestibule or the endolymphatic sac 23,34 . A study recommends leaving about 32% of the lateral portion of the IAC without manipulation to avoid compromising the labyrinth structures 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Já nos acessos suboccipitais, esta parte obscura varia de 2mm 16,17 até zero 18,19 , conforme a via de acesso aproxima-se da linha sagital mediana do crânio. Entretanto, requer-se uma progressiva retração do cerebelo e cérebro nestes acessos.…”
Section: Discussionunclassified